Fabric integrated wearable glove with a twisted string actuator for manual handling tasks - Jinhui An; Soah Park; Jeongmin Kim; Dongun Lee; Yumin Cho; Sumin Helen Koo; Dongjun Shin (Scientific Reports)
Abstract Wearable robotic gloves with grip-assistive functionality offer a promising solution for high-intensity manual tasks. However, achieving a balance among lightweight design, adequate force generation, and dexterous hand movement in wearable robotic gloves remains a significant challenge. In this study, we developed a fabric-integrated TSA-Glove to provide task-specific assistance while preserving dexterous movement. A high force-density Twisted String Actuator (TSA) was designed based on task-oriented parameters and strategically integrated into selected fabric materials to ensure efficient force transmission, flexibility, and lightweight performance. Additionally, an embedded routing design enhanced hand dexterity and TSA durability. The gloves were evaluated through grip force measurements, muscle activation analysis, and dexterity assessments. Compared to industrial gloves, the TSA-Glove demonstrated an 11.20% improvement in maximum grip force and a 18.02% smaller decrease in Maximal Voluntary Contraction (%MVC) values. The dexterity test further confirmed its improved performance, even with similar thickness. These results validate the TSA-Glove as a lightweight, task-optimized system, effectively supporting repetitive and physically demanding manual tasks.